2022
DOI: 10.3389/fimmu.2022.974364
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant COVID-19 vaccine based on recombinant RBD/Nucleoprotein and saponin adjuvant induces long-lasting neutralizing antibodies and cellular immunity

Abstract: SARS-CoV-2 has caused a global pandemic, infecting millions of people. An effective preventive vaccine against this virus is urgently needed. Here, we designed and developed a novel formulated recombinant receptor-binding domain (RBD) nucleocapsid (N) recombinant vaccine candidates. The RBD and N were separately expressed in E. coli and purified using column chromatography. The female Balb/c mice were immunized subcutaneously with the combination of purified RBD and N alone or formulated with saponin adjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In this context, it has been demonstrated that the protective immunity of certain types of vaccines could be enhanced by the addition or substitution of different adjuvants [ 120 , 121 ]. Between these adjuvants, saponins are one of the most widely used immunostimulants to boost vaccines because they may modify the activities of T cells and activate anti-gen-presenting cells (APCs), such as dendritic cells (DC), and induce Th1/Th2 adaptive immunoresponses (Th1 or cell-mediated immunity controlled by activated T cells, and Th2 or humoral immunity controlled by activated B cells and antibodies) or only Th2 response [ 36 , 49 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, it has been demonstrated that the protective immunity of certain types of vaccines could be enhanced by the addition or substitution of different adjuvants [ 120 , 121 ]. Between these adjuvants, saponins are one of the most widely used immunostimulants to boost vaccines because they may modify the activities of T cells and activate anti-gen-presenting cells (APCs), such as dendritic cells (DC), and induce Th1/Th2 adaptive immunoresponses (Th1 or cell-mediated immunity controlled by activated T cells, and Th2 or humoral immunity controlled by activated B cells and antibodies) or only Th2 response [ 36 , 49 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Resultsmentioning
confidence: 99%
“…Between these, adjuvant systems based on QS-21 have been widely suggested and studied as an alternative for boosting recombinant vaccines. These systems use the complete S protein as an immunogen [ 36 , 49 , 120 ], or its S1 domain [ 150 ] or only its receptor binding domain (RBD)/nucleocapsid (N) [ 122 ]. Currently, these adjuvant systems are being studied in clinical trials (i.e., still in progress), in which it is proposed to evaluate the safety, reactogenicity, and immune response against COVID-19 of a recombinant S protein-based vaccine with the QS-21 adjuvant (NCT04784767).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, refolded RBDs have demonstrated binding to SARS-CoV-2 antibodies [ 49 ] and the human ACE2 receptor [ 31 , 50 ], and their overall structure was similar to mammalian-derived products [ 31 , 53 ]. E. coli RBD vaccination in small animals with multiple adjuvants, including Al(OH) 3 + CpG ODN [ 51 ], Sigma Adjuvant System (Sigma-Aldrich) [ 47 ], TiterMax Gold (Sigma-Aldrich) [ 50 ], Alum [ 28 ], and Saponin [ 54 ], have shown high immunogenicity and the induction of neutralizing antibodies. Soluble proteins that are generally considered weak immunogens require formulation with potent adjuvants [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Priming of cross-reactive nucleoprotein-specific T cells alone was 60% protective [ 164 ]. Similarly, other teams also designed and developed multiple recombinant vaccines based on nucleoproteins [ 165 168 ].The results showed that recombinant vaccines could significantly increase the levels of serum neutralizing antibody and total immunoglobulin [ 165 ], and induce strong specific lymphocyte proliferative response and T cell response [ 165 ]. The antigen specificity level of interferon-γ in splenocytes of immunized mice increased [ 166 , 167 ].…”
Section: Introductionmentioning
confidence: 99%